Law, love, and freedom: From the sacred to the secular - TAN, Seow Hon (Institutional Knowledge at Singapore Management University, 2024)
In this book, published under a series on the intersection of law and Christianity, Neoh undertakes the ambitious project of exploring the concepts of law, love, and freedom to illuminate the moral vision which underlies our secular legal order.